"They can live in the desert but nowhere else": a history of the Armenian genocide - Suny, Ronald Grigor (Human rights and crimes against humanity, 2015)
Empire -- Armenians -- Nation -- Great Powers -- Revolution -- Counterrevolution -- War -- Removal -- Genocide -- Orphaned Nation -- Conclusion: Thinking about the Unthinkable : Genocide -- Historians Look at the Armenian Genocide : A Bibliographical Discussion